2011
DOI: 10.1063/1.3663868
|View full text |Cite
|
Sign up to set email alerts
|

Giant magneto-light output in three-phase magnetostrictive, piezoelectric, and electroluminescent composites

Abstract: Clear magneto-light output is obtained from a fabricated three-phase composite of magnetostrictive, piezoelectric, and electroluminescent materials. Electrical charges, attributable to the magnetoelectric effect, are induced when a magnetic field is applied to the magnetostrictive/piezoelectric layers. These induced electrical charges result in a light signal emanating from the electroluminescent layer, thereby accomplishing a magneto-light effect. Increasing the strength of the applied ac magnetic field or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Apart from our recent reports on luminescence controlled by electric eld, 50 and strain, 38 very recently, light emission is also demonstrated using a threephase composite made of magnetostrictive, piezoelectric, and EL layered materials. 76 The results showed that the brightness of light emissions was enhanced by increasing the applied ac magnetic eld. These latest results offer some perspective as to which areas optoelectronic applications can expect metal-ion doped luminescent thin lms to constitute a platform offering multi-functionality of novel optoelectronic devices.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from our recent reports on luminescence controlled by electric eld, 50 and strain, 38 very recently, light emission is also demonstrated using a threephase composite made of magnetostrictive, piezoelectric, and EL layered materials. 76 The results showed that the brightness of light emissions was enhanced by increasing the applied ac magnetic eld. These latest results offer some perspective as to which areas optoelectronic applications can expect metal-ion doped luminescent thin lms to constitute a platform offering multi-functionality of novel optoelectronic devices.…”
Section: Discussionmentioning
confidence: 98%
“…The ME properties of the Permendur/PZT composite may be further enhanced by increasing the interface coupling coefficient [23], the number (n) of magnetostrictive/piezoelectric layers (piezoelectric layers are electrically connected in series, series E E n α = α ) [24], and/or adopting a piezoelectric material with a higher piezoelectric coefficient such as (1-x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 (PMN-PT) [25].…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] These properties make these crystals suitable candidates for application to piezoelectric sensors, transducers, and actuators. [15][16][17] In general, the high SP effect occurs in materials with high primary piezoelectric coefficients. 9 The (1 À x)PMN-xPT crystals are therefore likely to have a high SP coefficient, which will, to a certain extent, reduce its practical piezoelectric coefficient, and this should be taken into account for accuracy in piezoelectric sensor/actuator applications.…”
mentioning
confidence: 99%